PROBLEMS WHICH IS ENCOUNTERED HR MANAGER WHEN RECRUITING STAFF - Лук’янчук, Олена (SWorldJournal, 2022)
The paper considers the main problems faced by the HR manager in his work. After each problem, options for solving the considered problems that the HR manager faces when recruiting staff for vacant positions are offered. The algorithm of actions of effect